ANALISIS BEBAN DAN STATUS PENCEMARAN BOD DAN COD DI KALI ASIN, SEMARANG - Kurnianti, Lelim Yelli; ., Haeruddin; Rahman, Arif (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2020)
Kali Asin is an important river for the drainage system in North Semarang. This river is often drained by domestic and industrial waste. The inclusion of these wastes can cause a decrease water quality marked by an increase Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) concentrations. The purpose of this study was to determine the load of BOD and COD pollution and assess the status of pollution using the Pollution Index Method based on Government Regulation Number 82 of 2001 class II. Sampling was carried on 17 December 2019-28 January 2020. Sampling was carried out three times, once in 3 weeks. The material used was water samples taken from three stations (estuary, middle of the settlement, and far from the settlement) based on regional characteristics, land use, and sources of pollution. The research method uses a survey method with the technique of determining the location of sampling using purposive sampling. Water quality variables analyzed were temperature, discharge, pH, DO, BOD, COD. Based on the research results, these variables mostly do not meet the quality standards such as BOD and COD variables. The results of the calculation of pollution load in terms of BOD and COD variables obtained an average number of 952.54 kg / day and 3,425.86 kg / day. The results of the pollution index calculation at stations A, B, and C are 3.88; 3.78 and 3.53. The level pollution of Kali Asin was categorized in mild contamination.Â Keywords: Pollution Load, BOD, COD, Pollution Index, Kali Asin